The Effect of Mind Mapping in Descriptive Text toward Writing Achievement of Grade X Students - Farida Lutfia (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2020)
Abstract: Writing is a way to deliver our ideas in the form of text. The writer can deliver everything on their minds in paper so that their writings can be written by everybody else. Writing is good for people who have less confidence in conveying their feelings. Since, we do not only communicate with others people through speaking but also by means of writing. In fact, many of students gain some difficulties when they write in paper less background knowledge, grammatical problem, need long time to create idea, there is no feed back, and way to make a coherence paragraph. A lot of technique that have been designed by the researcher and the teachers, and every technique has some benefits and compatibility in certain text. One of the appropriate technique for writing descriptive text is mind mapping. The teachers can apply mind mapping as the alternative in learning and teaching descriptive text. In this present study, the researcher tried to know the effectiveness of mind mapping in writing descriptive text of vocational high school students to get better performance.This research was conducted in grade X students at SMK NU Sunan Ampel Poncokusumo with 22 students as the experimental group and 22 students as the control group of the research. Sample was determined randomly. The researcher collected the data by applied pre-test, treatment, and post-test in this study. Pre-test was delivered in the first meeting before the students received the treatment. In this case, pre-test was to found out the students’ writing skill both groups before gotten the treatment. Mind mapping was given to the experimental group as the treatment whereas the control group gained conventional technique as the treatment. In last part, the students from both groups obtained post-test to measure some changes of the students’ writing ability after received the treatment. Furthermore, the experimental group and the control group acquired same pretest and post-test.This study used a quasi-experimental design. So, the data needed in answering the research problem would be in quantitative data. Then, for reaching the purpose of the study, the data was analyzed using SPSS Statistical 20 program. Based on the result, the mean score of experimental group was 69.000 while the mean score of control group was 61.909. The independent sample t-test pointed out that the level of significance (2-tailed) of this study was 0.046. It means that the level of significance was lower than 0.05. Therefore, it showed that there is sifnificant different score of students’ achievement in writing descriptive text that was taught through mind mapping technique and without mind mapping technique.Based on the result of data analysis, it can be concluded that the students who were taught using mind mapping got better score than those who were not. Also, it can be said that mind mapping is more effective for students’ writing achievement than conventional technique. Therefore, the teacher is suggested to apply mind mapping as a great technique in teaching writing process especially for descriptive text. Since mind mapping can help the students to obtain ideas and make a coherence paragraph easily. The suggestion for the next researcher is can be better to apply mind mapping in other skills. Key words: writing achievement, descriptive text, mind mapping, effect